Factors Associated with Post-Non Hemorrhagic Stroke Depression: a cross-sectional study - Putri, Nirmala Rumaja; Upoyo, Arif Setyo; Sumeru, Annas (Universitas Muhammadiyah Yogyakarta, 2023)
Background: Post-stroke patient depression can result in delays in stroke recovery and healing. The degree of severity of stroke will cause neurological deficits which can become stressors that will affect individual coping mechanisms.Objective: This research aims to analyze factors associated with non-hemorrhagic post-stroke depression.Methods: Analytical observational with a cross-sectional approach. The research was conducted at the Neurology Clinic of RSUD dr. R. Goeteng Taroenadibrata Purbalingga. The population is 435 post-stroke non-hemorrhagic patients. The sample is 104 respondents with the sampling technique used consecutive sampling. The instruments used were the Brief COPE, NIHSS, and PHQ-9. Bivariate analysis used the Kendall-Tau correlation test.Results: The majority of respondents were elderly, male, primary school education level/equivalent, married, live with husband/wife and children, left hemisphere lesion location, had stroke duration 2 years, did not experience recurrent strokes, hypertension, had problem-focused coping and mild stroke severity with varying degrees of depression. Age, gender, marital status, living together, location of the lesion, duration of stroke, stroke frequency, comorbidities and coping mechanisms were not significantly related (p0.05) while education level and stroke severity was significantly associated with post-stroke depression (p0,05).Conclusions: There is a significant relationship between education level and severity of stroke with post-stroke depression. Nurses can also motivate patients to always take medication regularly, increase patient knowledge about stroke and depression, or implement non-pharmacological therapy such as Range of Motion (ROM) so that they can help reduce the severity of a stroke and prevent or reduce the occurrence of depression after non-hemorrhagic stroke.